m^2-7m+12 = (m-3)(m-4)
m^3-2m^2-2m-3 = (m-3)(m^2+m+1)
so, LCM = (m-3)(m-4)(m^2+m+1)
Now try the others. What do you get?
Find the LCM of the following :
1)m^2 - 7m + 12 and m^3 - 2m^2 - 2m -3
2) (r - 1) ^3 and r^4 + r^2 +1 and r^3 - 1
3) 3(p^3 - 1) and (4p^2 - 1 ) and 6(2p^2 + 3p - 2 )
4 answers
can you show the process. how you got
m^3-2m^2-2m-3 = (m-3)(m^2+m+1) . pls
m^3-2m^2-2m-3 = (m-3)(m^2+m+1) . pls
just a little synthetic division trying to find a root. Cubics are not always easy to factor by inspection.
can you show the process pls.